An Examination of Standardized Letters of Recommendation Rating Scales Among Neurosurgical Residency Candidates During the 2020-2021 Application Cycle. Issue 6 (8th October 2021) - Feldman, Michael J; Ortiz, Alexander V; Roth, Steven G; Dambrino, Robert J; Yengo-Kahn, Aaron M; Chitale, Rohan V; Chambless, Lola B
Abstract: BACKGROUND: Letters of recommendation (LORs) are historically an important, though subjective, component of the neurosurgery residency application process. Standardized LORs (SLORs) were introduced during the 2020 to 2021 application cycle. The intent of SLORs is to allow objective comparison of applicants and to reduce bias. OBJECTIVE: To examine the utility of SLORs during this application cycle. We hypothesized that "grade inflation" and poor inter-rater reliability, as described by other specialties using SLORs, would limit the utility of SLORs in their current form. METHODS: This cross-sectional study analyzed all SLORs submitted to a single neurosurgery residency program over the 2020 to 2021 cycle. Data from 7 competency domains and the overall rating were recorded and stratified by academic category of letter writer. Inter-rater reliability was evaluated using Krippendorff's alpha. RESULTS: One or more SLORs was submitted as part of 298 of 393 applications (76%). Approximately 58.3% of letters written by neurosurgery chairpersons rated a given applicant as being within the top 5% across all competencies. Approximately 44.4% of program director letters similarly rated applicants as amongst the top 5%, while 73.2% and 81.4% of letters by other neurosurgeons and general surgery evaluators, respectively, rated applicants in the top 5%. Inter-rater reliability was poor (<0.33) in all rating categories, including overall (α = 0.18). CONCLUSION: The utility of the first iteration of SLORs in neurosurgery applications is undermined by significant "grade inflation" and poor inter-rater reliability. Improvements are necessary for SLORs if they are to provide meaningful information in future application cycles.